Compact and low‐cost reflectometer using a LH‐NLTL frequency translator. Issue 4 (April 2017) - Park, Soonwoo; Kim, Jingyu; Kim, Hongjoon
ABSTRACT: In this study, we fabricated a low‐cost, miniaturized reflectometry system using a left‐handed nonlinear transmission line (LH‐NLTL) and compared its performance with that of a commercial vector network analyzer (VNA). In the system, we used the LH‐NLTL as a frequency translator to replace a bulky and expensive frequency synthesizer. In addition, instead of using a bulky broadband coupler, we used a compact resistive coupler to minimize the size of the overall system. To improve system accuracy, we employed a four‐port network calibration equation. The resulting system exhibits highly similar performance compared to a commercial VNA. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:873–876, 2017